Analysis of the Effects of Firm Size and Net Income on Stock Prices With Earnings Per Share as a Moderating Variable in Energy Sector Companies - Lili Juniyanti; Najma Alkamila; Arinda Nafisa; Nur Baiti Jannati (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to determine the effect of firm size and net income on stock prices, as well as to test whether earnings per share can serve as a moderating variable in the relationship between these two variables and stock prices. Methodology: This study employs a quantitative approach with a sample of 66 financial statements from energy sector companies listed on the Indonesia Stock Exchange, selected using purposive sampling. Data analysis was conducted using Moderated Regression Analysis with the aid of IBM SPSS software to test the influence and moderating effects among the variables. Main Findings: The results of the study indicate that firm size has no effect on stock prices, whereas net income has a positive effect on stock prices. Furthermore, earnings per share does not moderate the effect of firm size on stock prices or the effect of net income on stock prices; therefore, it does not serve as a moderating variable in this study of companies in the energy sector. Novelty/Originality of this study: This study reexamines the effects of firm size and net income on stock prices, with earnings per share serving as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange during the 2024–2025 period. It aims to evaluate the moderating role of earnings per share and provide updated empirical evidence on these relationships.